On the Economics and Politics of Refugee Migration - Christian Dustmann; Francesco Fasani; Tommaso Frattini; Luigi Minale; Uta Schönberg (Institute for the Study of Labor (IZA), 2016)
This paper provides a comprehensive analysis of refugee migration, with emphasis on the current refugee crisis. After first reviewing the institutional framework laid out by the Geneva Convention for Refugees, we demonstrate that, despite numerous attempts at developing a common European asylum policy, EU countries continue to differ widely in interpretation and implementation. We then describe key features of the current refugee crisis and document the overall magnitudes and types of refugee movements, illegal border crossings, and asylum applications to EU member states. We next turn to the economics of refugee migrations, contrasting economic and refugee migrants, discussing the trade-offs between long-term asylum and temporary protection, and highlighting the economic advantages of increasingly coordinating the different national asylum policies. Finally, we illustrate the economic integration of past refugee migrants to EU countries and conclude with several policy recommendations.
Keywords: F22; J15; J61; 330; asylum policy; asylum seekers; refugee crisis